2002
DOI: 10.1080/01485010290099255
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Quality of Rabbit Semen in 14 Consecutive Ejaculates Obtained Every 15 Minutes

Abstract: Modifications of semen quality related to ejaculation frequency is one of the most important and neglected factors from the standpoint of artificial insemination or sperm competition. New Zealand white rabbits (Oryctolagus cuniculus) offer an advantageous experimental model because they have characteristic sexual behavior, they present rapid ejaculation after a single intromission, they have a very short interval between successive ejaculations, and semen can be easily collected. The authors studied the modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 7 publications
0
16
1
Order By: Relevance
“…Some studies have found that, after 5-6 successive ejaculations, the buck has almost no sperm in the ejaculate (Ambriz et al, 2002;Oshio et al, 1986). This finding is at odds with our behavioural data in which the ejaculatory motor pattern can exceed 43 on a given test day.…”
Section: Discussioncontrasting
confidence: 57%
“…Some studies have found that, after 5-6 successive ejaculations, the buck has almost no sperm in the ejaculate (Ambriz et al, 2002;Oshio et al, 1986). This finding is at odds with our behavioural data in which the ejaculatory motor pattern can exceed 43 on a given test day.…”
Section: Discussioncontrasting
confidence: 57%
“…The effect of successive ejaculate collection has been investigated in a number of terrestrial species, such as horses (Squires et al, 1979; Pickett et al, 1985), bulls (Foote, 1978), dogs (England, 1999), cats (Tanaka et al, 2000), and rabbits (Ambriz et al, 2002). Comparison between results of these species and the results of this study must be made with caution because the time interval between the collection of consecutive ejaculates and the number of collection sessions per week differ.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of such competition, notwithstanding mating order effects, depends on a "raffle" or "lottery" principle; that is, a particular male can increase the probability of siring a female's offspring by inseminating more sperm (Parker, 1970(Parker, , 1990. The costs of ejaculate production are nontrivial, however (Dewsbury, 1982;Nakatsuru & Kramer, 1982;Olsson, Madsen, & Shine, 1997), and repeated ejaculation can lead to sperm depletion (Ambriz et al, 2002;Preston, Stevenson, Pemberton, & Wilson, 2001). Therefore, males must trade off ejaculate production costs against the potential benefits of delivering large numbers of sperm.…”
Section: Sperm Competition In Nonhuman Speciesmentioning
confidence: 99%